Recognition and Relevance of Anti-DFS70 Autoantibodies in Routine Antinuclear Autoantibodies Testing at a Community Hospital - Carter, John B.; Carter, Sara; Saschenbrecker, Sandra; Goeckeritz, Bruce E. (Frontiers in Medicine, 2018)
Anti-nuclear autoantibodies (ANA) displaying a dense fine speckled pattern (DFS, ICAP AC-2) on HEp-2 cells are frequently observed in clinical laboratory referrals, often associated with anti-DFS70 specificity. Anti-DFS70 positive patients rarely develop systemic autoimmune rheumatic disease (SARD), especially in the absence of clinical evidence or additional ANAs, prompting suggestions that an isolated DFS70-specific ANA may be an exclusionary finding for SARD. In this study, the frequency and diagnostic significance of anti-DFS70 autoantibodies was investigated in a community hospital cohort of patients undergoing routine ANA testing. ANA screening was performed by HEp-20-10-based indirect immunofluorescence, followed by anti-extractable nuclear antigen (ENA) profiling using a multiparametric line immunoassay (LIA). Of 6,511 patient samples tested for ANA in 2016, the DFS pattern was identified in 1,758 (27.0%), 720 (41.0%) of which were anti-DFS70 positive by LIA. Of these, 526 (73.1%) revealed isolated anti-DFS70 reactivity, while 194 (26.9%) showed additional ENA specificities. Among 1,038 anti-DFS70 negative or borderline samples, 778 (75.0%) were ENA profile negative, while the remaining 260 (25.0%) showed a varied presence of other ENA specificities. Chart reviews of patients with an isolated anti-DFS70 ANA affirmed that ANA-related SARD is rare in the absence of clinical evidence or other ENA specificities, there being no case thus far identified. Rheumatoid arthritis patients occasionally had an isolated anti-DFS70 ANA, and were positive for rheumatoid factor and anti-cyclic citrullinated peptide antibodies. In conclusion, the recognition of a DFS ANA pattern using a mitotic-rich HEp-2 substrate, followed by confirmation of anti-DFS70 specificity should be a routine ANA testing service. Use of an expanded ENA profile and clinical correlation is necessary to affirm the “isolation” of anti-DFS70 as the cause of an ANA. Recognition of isolated anti-DFS70 ANA enables reassurance of patients that SARD is unlikely, thus avoiding referral for more extensive testing. The presence of significant elevations of other ANAs may reflect SARD and warrants close clinical correlation and follow-up.